ขออนุญาตลงเฉลยครับผม
55555 - 1 = (51111 - 1)(54444 + 53333 + 52222 + 51111 + 1) = (51111 - 1)(54444 + (6 - 5).53333 + (9 + 2 - 10).52222 + (6 - 5).51111 + 1) = (51111 - 1)[(54444 + 9.52222 + 1 + 6.53333 + 2.52222 + 6.51111) - (5.53333 + 10.52222 + 5.51111)] = (51111 - 1)[((52222)2 + (3.51111)2 + 12 + 2(52222.3.51111 + 52222.1 + 3.51111.1)) - (53334 + 2.52223 + 51112)] = (51111 - 1)[(52222 + 3.51111 + 1)2 - ((51667)2 + 2.51667.5556 + (5556)2)] = (51111 - 1)[(52222 + 3.51111 + 1)2 - (51667 + 5556)2] = (51111 - 1)(52222 - 51667 + 3.51111 - 5556 + 1)(52222 + 51667 + 3.51111 + 5556 + 1)
จากคุณ |
:
TIYHz
|
เขียนเมื่อ |
:
วันวิทยาศาสตร์แห่งชาติ 54 23:15:15
|
|
|
|